Inclusive Growth in Northern and Southern Central Java - Hayu Wuranti (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
Inclusive growth is one of the visions of sustainable development.Â  Economic growth of a region is said to be inclusive if it is able to reduce poverty, reduce inequality and absorb more labour. Central Java is one of the regions with fairly high economic growth but has various social problems. Therefore, this study wants to see the inclusiveness of economic growth in the North and South Central Java region. The research is based on data from 35 districts in Central Java, which adopts the concept formulated by Klasen (2010) regarding the Poverty-Equivalent Growth Rate (PEGR). The research shows that during the 2018-2020 period, Central Java had not consistently has inclusive growth. Meanwhile, inclusive growth for the three indicators in 2018 mostly occurred in the northern part of Central JavaÂ  but was more and more balanced.